Dstac Regulates Excitation-Contraction Coupling in Drosophila Body Wall Muscles - Hsu, I-Uen; Linsley, Jeremy W.; Reid, Lilly E.; Hume, Richard I.; Leflein, Ari; Kuwada, John Y. (Frontiers in Physiology, 2020)
Stac3 regulates excitation-contraction coupling (EC coupling) in vertebrate skeletal muscles by regulating the L-type voltage-gated calcium channel (Cav channel). Recently a stac-like gene, Dstac, was identified in Drosophila and found to be expressed by both a subset of neurons and muscles. Here, we show that Dstac and Dmca1D, the Drosophila L-type Cav channel, are necessary for normal locomotion by larvae. Immunolabeling with specific antibodies against Dstac and Dmca1D found that Dstac and Dmca1D are expressed by larval body-wall muscles. Furthermore, Ca2+ imaging of muscles of Dstac and Dmca1D deficient larvae found that Dstac and Dmca1D are required for excitation-contraction coupling. Finally, Dstac is required for normal expression levels of Dmca1D in body-wall muscles. These results suggest that Dstac regulates Dmca1D during EC coupling and thus muscle contraction.